Consumer Perception of Host Interaction in Live Streaming Shopping: an Analysis of Purchase Intention and Impulse Buying in Indonesian Live Streaming Media - Muna, Khanna Nailil; Setyawan, Anton Agus (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The rapid growth of live streaming shopping in Indonesia has made it essential to understand the factors influencing consumer purchasing decisions in this unique retail format. This study aims to examine the impact of host interaction on purchase intention and impulse buying behavior among Indonesian consumers in Generation Z’s and Millenials. Methodology: This study employed a quantitative research method using online questionnaire with 210 Indonesian respondents who had previously watched and shopped on live streaming shopping platforms. This research uses Smart PLS 4 with PLS-SEM model and bootstrapping analysis to determine the moderating effect on the research variables. Results: This study found that Generation Z's purchase intention and impulse buying are more influenced by engaging live hosts compared to Millennials. Personalized and entertaining host interactions significantly increased purchase intention and impulse buying. This research also indicates that positive and engaging live host interactions can enhance consumers' purchase intention in live streaming shopping. Application/Originals/Value: These findings suggest that live streaming platforms should invest in training hosts to deliver engaging and interactive experiences. Furthermore, this research contributes to the emerging body of knowledge on consumer behavior in the digital marketplace.